2014
DOI: 10.1093/eurheartj/ehu028
|View full text |Cite
|
Sign up to set email alerts
|

Early management of atrial fibrillation to prevent cardiovascular complications

Abstract: Atrial fibrillation (AF) is generally considered a progressive disease, typically evolving from paroxysmal through persistent to 'permanent' forms, a process attributed to electrical and structural remodelling related to both the underlying disease and AF itself. Medical treatment has yet to demonstrate clinical efficacy in preventing progression. Large clinical trials performed to date have failed to show benefit of rhythm control compared with rate control, but these trials primarily included patients at lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
137
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(152 citation statements)
references
References 93 publications
8
137
1
6
Order By: Relevance
“…It has been suggested that earlier aggressive intervention to maintain sinus rhythm, including AF ablation if needed, may aid to prevent 'chronicization' of AF and improve long-term outcomes. 501 A large-scale multicentre trial is presently testing this idea. 502 The true impact of atrial cardiomyopathies on the success of catheter ablation has not been elucidated.…”
Section: Impact Of Catheter Ablation On Atrial Pathologymentioning
confidence: 99%
“…It has been suggested that earlier aggressive intervention to maintain sinus rhythm, including AF ablation if needed, may aid to prevent 'chronicization' of AF and improve long-term outcomes. 501 A large-scale multicentre trial is presently testing this idea. 502 The true impact of atrial cardiomyopathies on the success of catheter ablation has not been elucidated.…”
Section: Impact Of Catheter Ablation On Atrial Pathologymentioning
confidence: 99%
“…10,11 Each AF episode requires initiation by a trigger acting on a vulnerable substrate. This vulnerable substrate is at least partly determined by genetic factors.…”
Section: Conceptual Framework Af As a Progressive Diseasementioning
confidence: 99%
“…15 About 5% of patients with pAF progress to persistent forms each year. 11 Further progression occurs at increasing rates, with 35% to 40% of patients with persistent AF developing permanent AF <1 year. 4 The progression rate is lowest in young patients without associated heart disease (lone AF), amounting to 1% to 3% per year.…”
Section: Conceptual Framework Af As a Progressive Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…AF is generally considered a progressive disease, with episodes increasing in frequency and/or duration over time, resulting in a transition from paroxysmal (lasting \7 days and spontaneously converting to sinus rhythm) AF (pAF) to persistent AF (lasting [7 days or requiring cardioversion), long-lasting persistent (chronic) AF (cAF), and permanent AF [12,20]. Although the current AF classification was not developed based on underlying pathophysiological mechanisms, there are important differences in the molecular and cellular electrophysiology of pAF and cAF patients [30,31].…”
mentioning
confidence: 99%